China-Pakistan Economic Corridor (CPEC) and Questions on Pakistan's Economic Stability. Issue 2 (3rd March 2020) - Ul Hassan, Yaqoob
Abstract: This article begins with a discussion on how the China-Pakistan Economic Corridor (CPEC) is viewed differently by different political parties as well as by the civilian and military establishments in Pakistan. The discussion then turns to Pakistan's current economic conditions and examines whether CPEC has the potential to boost the Pakistan economy or contribute to the worsening of its economic conditions. This article also discusses how CPEC seeks to maintain a balance between geo-economic and geopolitics. The article throws light on how CPEC has affected the internal political dynamics within Pakistan, and why the work on CPEC has slowed down.